2019
DOI: 10.1002/fuce.201800152
|View full text |Cite
|
Sign up to set email alerts
|

Performance Degradation of Proton Exchange Membrane Fuel Cell Caused by an Accelerated Stress Test

Abstract: Proton exchange membrane fuel cell (PEMFC) experiences inevitably performance decay due to various mechanisms. Among those, carbon corrosion is extremely detrimental. In this study, an accelerated stress test (AST) is conducted to a single cell to mimic the conditions when carbon corrosion occurs. The cell performance is characterized intermittently, and the experiment results show although electrochemical active area (ECA) decreases continuously from beginning‐of‐life (BOL) due to carbon corrosion at catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…First, a preliminary test was executed by keeping the fuel cell at constant current density: 0.5 A cm −2 was selected as a representative value for real applications [28] and kept fixed for 1000 h at 60 • C and RH 80-60%. Moreover, an ex situ mechanical acceler-ated stress test (AST) was also designed on the same samples in order to have a faster assessment of the durability of the prepared components in terms of mechanical resistance without performing continuous tests for thousands of hours, which is a common practice also for electrochemical ASTs evaluating degradation of different fuel cell components, such as electrodes or membrane [34,35]. Indeed, it has been demonstrated that the most detrimental degradation mechanism for GDMs is the mechanical one, which is due to both the continuous flow of the gaseous streams and the presence of water causing the detachment of the MPL surface carbon [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a preliminary test was executed by keeping the fuel cell at constant current density: 0.5 A cm −2 was selected as a representative value for real applications [28] and kept fixed for 1000 h at 60 • C and RH 80-60%. Moreover, an ex situ mechanical acceler-ated stress test (AST) was also designed on the same samples in order to have a faster assessment of the durability of the prepared components in terms of mechanical resistance without performing continuous tests for thousands of hours, which is a common practice also for electrochemical ASTs evaluating degradation of different fuel cell components, such as electrodes or membrane [34,35]. Indeed, it has been demonstrated that the most detrimental degradation mechanism for GDMs is the mechanical one, which is due to both the continuous flow of the gaseous streams and the presence of water causing the detachment of the MPL surface carbon [28].…”
Section: Methodsmentioning
confidence: 99%
“…ment of the durability of the prepared components in terms of mechanica out performing continuous tests for thousands of hours, which is a com for electrochemical ASTs evaluating degradation of different fuel cell c as electrodes or membrane [34,35]. Indeed, it has been demonstrated th mental degradation mechanism for GDMs is the mechanical one, which continuous flow of the gaseous streams and the presence of water causin of the MPL surface carbon [28].…”
Section: Morphologymentioning
confidence: 99%
“…The aging test protocol is used because the consequences of carbon corrosion in PEMFC are in diverse aspects, including kinetic and non-kinetic, in CL and also MPL/GDL. The experimental method has been commonly used in previous studies [18][19][20]30 and proven to achieve comprehensive accelerated stress testing for PEMFCs. The cell performance decay rate is significantly accelerated in AST compared to that in normal operations.…”
Section: Electrochemical Characterization and Aging Testmentioning
confidence: 99%
“…The collapse of porous structure and reduction in thickness caused by carbon loss in CCLs, , as well as the increased hydrophilicity of carbon surface due to oxygen-containing functional groups with the concentration of liquid water, would impede molecular and Knudsen oxygen transport process in the CCLs, thereby affecting r bulk . Regarding the governing role of TPBs in the oxygen transport process, the carbon support corrosion in CCLs plays a critical role in determining the interface between carbon/Pt and the ionomer, thus affecting R local .…”
Section: Introductionmentioning
confidence: 99%